Buffer Management for Colored Packets with Deadlines - Azar, Yossi; Feige, Uriel; Gamzu, Iftah; Moscibroda, Thomas; Raghavendra, Prasad (SPAA 2009: 21st ACM Symposium on Parallelism in Algorithms and Architectures, Calgary, Alberta, Canada, 2009)
We consider buffer management of unit packets with deadlines for a multi-port device with reconfiguration overhead. The goal is to maximize the throughput of the device, i.e., the number of packets delivered by their deadline. For a single port or with free reconfiguration, the problem reduces to the well-known packets scheduling problem, where the celebrated earliest-deadline-first (EDF) strategy is optimal 1-competitive. However, EDF is not 1-competitive when there is a reconfiguration overhead. We design an online algorithm that achieves a competitive ratio of 1 − o(1) when the ratio between the minimum laxity of the packets and the number of ports tends to infinity. This is one of the rare cases where one can design an almost 1-competitive algorithm. One ingredient of our analysis, which may be interesting on its own right, is a perturbation theorem on EDF for the classical packets scheduling problem. Specifically, we show that a small perturbation in the release and deadline times cannot significantly degrade the optimal throughput.This implies that EDF is robust in the sense that its throughput is close to the optimum even when the deadlines are not precisely known.